1996
DOI: 10.1159/000129479
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intraperitoneal 5-Fluorouracil Plus Folinic Acid on the Healing of Colonic Anastomoses in Rats

Abstract: We studied the effects of intraperitoneal 5-fiuorouracil (5-FU) administration with or without the addition of folinic acid (FA) on the healing of colonic anastomoses in rats immediately after surgery. Sixty-three male Wistar rats were subjected to colonic anastomosis. During surgery, the rats were randomized into one of three groups. Therapy was administered as an intraoperative intraperitoneal injection which was repeated once daily for the first 2 postoperative days. A 0.9% NaCl solution was administered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
44
0
29

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(85 citation statements)
references
References 10 publications
12
44
0
29
Order By: Relevance
“…In concordance with our results, Ersoy et al did not find any significant influence of 5-fluorouracil on the connective tissue remodeling reflected as collagen content changes [39]. The detrimental effects of 5-fluorouracil have also been demonstrated by other researchers [26,40,41]. In the study by Graf et al, it was found to significantly impair anastomosis healing [40].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In concordance with our results, Ersoy et al did not find any significant influence of 5-fluorouracil on the connective tissue remodeling reflected as collagen content changes [39]. The detrimental effects of 5-fluorouracil have also been demonstrated by other researchers [26,40,41]. In the study by Graf et al, it was found to significantly impair anastomosis healing [40].…”
Section: Discussionsupporting
confidence: 92%
“…The methodology used in most of those studies relied on the analysis of the macroscopic status of the anastomosis. Additionally, bursting strength, intensity of local inflammation, and collagen content have been used by some authors [25,26]. The results of those studies are not completely concordant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more pronounced inflammatory response was noted with intraperitoneal administration of 5-FU and with the combined treatment. This inflammatory reaction was also reported when 5-FU was administered intraperitoneally in the rat during surgery or early postoperatively [36,37].…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, the healing process can be significantly inhibited and therefore a rupture in the colon anastomoses may occur (20).…”
Section: Discussionmentioning
confidence: 99%